ASUHAN KEBIDANAN PADA REMAJA NN X PENGKONSUMSIAN MINUMAN JAHE TERHADAP NYERI HAID DI PUSKESMAS TANJUNG BALAI - Maryati; Devy Lestari Nurul Aulia; Sarmauli Franshisca Sihombing (Universitas Batam, 2023)
Primary dysmenorrhea most often occurs in young women (primary dysmenorrhea). About 50% of women of reproductive age experience dysmenorrhea. Young women who experience severe menstrual pain can disrupt daily activities including school, college and work. Efforts to deal with menstrual pain (dysmenorrhea) can be done by non-pharmacological to help reduce menstrual pain including with a number of spices, one of which is the consumption of ginger. The purpose of this study is to provide comprehensive and sustainable midwifery care during adolescence for women. Research method The type of research used in the preparation of practice reports is descriptive research using the case study method, conducted at the Tanjung Balai Karimun Health Center in January 2023. The data collection method is participatory observation, interviews, measurements, documentation. Research results show that menstrual pain (dysmenorrhea) after being given ginger drink has a significant decrease in pain levels Conclusion In the final stage of preparing a practice report with Midwifery Care for Adolescents Ms X Consumption of Ginger Drink Against Menstrual Pain at the Tg Balai Karimun Health Center in 2023.